A prospective study of subaxial spine injuries: An armed forces experience - Vikas Maheshwari; Maneet Gill; Aishik Mukherjee; Rushikesh Gadhavi (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2020)
Introduction: Cervical spine injuries account for 3% of all polytrauma patients and can lead to quadriplegia, significant functional loss, and permanent disability. A large spectrum of such cases requires surgical decompression and reconstruction with variable neurological outcomes. Aims and Objectives: The aim of the study was to critically review the subaxial cervical spine injury cases managed surgically with different types of implants at a tertiary level armed forces hospital and analyze their postoperative outcomes. Methods: A prospective analysis of patients (n = 85) of subaxial cervical spine injury was carried out between October 2014 and December 2017. The last patient of our study on July 17 was followed for 5 months. Surgical decompression and stabilization were done in 71 patients whereas 14 patients were managed conservatively. Pre- and post-operative neurological outcome was assessed by the American Spinal Injury Association (ASIA) score. Results: There were 81 men and 04 women whose mean age was 39 years (range 16–78 years). The most common cause of injury was road traffic accidents (45%, n = 38). C5-C6 was the most common site of injury 46% (n = 39). ASIA Grade C (n = 27, 32%) was the most common presentation. Seventy-one cases were treated surgically; 95% (n = 68) of through the anterior approach, 2 by the posterior approach and one by a combined approach. Of the 44 patients operated within 24 h of injury, 19 (43%) had a two-grade improvement in their ASIA scores, 5 (11%) had a one-grade improvement and the remaining 20 showed no change. Only one patient out of 27 patients operated 24 h after the injury showed improvement in ASIA grade. Conclusion: Subaxial cervical spine injuries are complex and a definite treatment algorithm is still a work in progress. However, early surgical decompression and stabilization lead to good neurological outcome in the majority of cases.